Application of supervisory control theory to theme park vehicles - Forschelen, Stefan T. J. (2013)
Due to increasing system complexity, time-to-market and development costs reduction, new engineering processes are required. Model-based engineering processes are suitable candidates because they support system development by enabling the use of various model-based analysis techniques and tools. As a result, they are able to cope with complexity and have the potential to reduce time-to-market and development costs. Moreover, supervisory control synthesis can be integrated in this setting, which can further contribute to the development of control systems. To evaluate the applicability of recently developed supervisor synthesis techniques and to show how they can be integrated in an engineering process, a theme park vehicle is chosen as a case study. The supervisor synthesized for the theme park vehicle has successfully been implemented and integrated in the existing resource-control platform.